Indigenous Cosmologies in Light of New Epistemological and Political Trends of the Global South - Terčelj, Mojca (Poligrafi, 2021)
The essential difference between indigenous religions and world religions is in the understanding of the “man-Nature” relationship. While the former perceive man as an equal actor in the establishment of cosmic harmony, placing him alongside all other living and non-living beings of creation, the latter place him in the centre of the world. The Christian religious tradition on the one side, and the Cartesian ontological dualism and methodological empiricism on the other, have strongly influenced the development of Western scientific thought. Over the past decades, the social sciences and humanities have made a great step forward: contributing to new interpretations of global economic and social laws, as well as of the hybridisation of ethnic identities, and starting to cooperate more closely with empirical sciences. The problem arises when self-indulgent introspection disqualifies any other type of knowledge as “non-scientific,” “local,” “romantic,” imperfect. At the beginning of the 21st century, the indigenous cosmology entered the political discourse and ideology of numerous social movements of the Global South. Based on a comparative analysis of three concrete indigenous cosmological and religious models (man vs. Nature relationship), this article seeks to draw attention to the need for a pluralism of mental concepts and social practices.